Factors of indigenous community tourism business success for the Mhong entrepreneurs in Thailand / B Chartrungruang ... [et al.] - Chartrungruang, B; Wattanalaungarun, W; Sa-Ingthong, K; Hanafiah, M.H.M; Zamzuri, N.H. (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
To be successful in businesses for the indigenous entrepreneurs has been very hard and rare to find, tourism businesses since the seasonal nature of the businesses and very little support and knowledge. This study explored the factors of indigenous community tourism business success for the Hmong tourism entrepreneurs in Thailand with a qualitative approach through interviews. The samples were 10 indigenous community entrepreneurs from Mhong People village in Chiang Mai who participated in the tourism-related businesses. This community has had several rewards and has had the most business ability among all hill tribes and made it the richest community. The data triangulation involves using 3 sources of data in an investigation was for the research validity. The ATLAS.ti qualitative data analysis software was used to create the networks and found the definition of business success in their viewpoints that are not concerned about monetary issues, as well as the factors of their indigenous community tourism business success. The findings have been worthwhile and beneficial for other indigenous communities in the similar settings.